Acute Exposure to Textile Waste Water Altered the Reproduction Biomarkers in Clarias gariepinus Broodstock - Abiola Fadilat Durojaiye; Nathanael Akinsafe Bamidele; Musa Dabo; Adijat Remilekun Moshood (Universitas Gadjah Mada, 2023)
This study was prompted by an earlier study that revealed the absence of gonads in all fish species caught around the Itoku tributary of the Ogun River, an area known for active textile activities. Thus, this study investigated the effect of textile wastewater on reproduction biomarkers in African catfish broodstock. Male and female broodstock were exposed to varying pre-determined concentrations (0ppb-T0, 0.5ppb-T1, 0.35ppb-T2, 2ppb-T3) of the textile wastewater for a period of 96 hours. Water quality parameters, seminal/ovarian hormones, metabolites, ions, oxidative, enzymes, and sperm viability were assayed. The water quality parameters of the wastewater indicated varying degrees of physical and chemical pollution. The values of hormones were significantly different (p<0.05) although a trend was not observed. Prolactin, however, showed a marked difference statistically across the treatments in the male broodstock while a reverse trend was observed in the female broodstock. The values recorded for seminal metabolites increased significantly compared to the control except for T3 for cholesterol and T1 glucose which were significantly lower than the control. In the female broodstock, the values for glucose and creatinine significantly increased compared to the control. Seminal ions evaluated showed significant differences across treatments. Except for T1, there was a significant reduction observed in the values of sodium, chloride, and calcium compared to the control. For ovarian ions, a significant increase was recorded across the treatments compared to the control. However, sodium recorded a significant decrease compared to the control except for T3 where the value was higher than the control. In the male broodstock, aspartate aminotransferase and alanine aminotransferase values were significantly lower compared to control while an opposite trend was observed in the female broodstock. The concentration of sperm and life- to-death ratio significantly reduced across treatments compared to the control. These results indicate that the textile wastewater altered the reproduction biomarkers in the male and female broodstock. The implication of this is that reproduction in fish might become a challenge in textile wastewater polluted Itoku tributary of the Ogun River.